2013
DOI: 10.3144/expresspolymlett.2013.82
|View full text |Cite
|
Sign up to set email alerts
|

Development of bio-based thermoplastic polyurethanes formulations using corn-derived chain extender for reactive rotational molding

Abstract: Abstract. Partly bio-based segmented thermoplastic polyurethane (TPU) formulations were developed to fulfill the requirements of the reactive rotational molding process. They were obtained by one-shot bulk polymerization between an aliphatic diisocyanate (1,6-hexamethylene diisocyanate), a polyether polyol as macrodiol (polyethylene glycol) and a biobased corn-derived 1,3-propanediol as chain extender (CE), in presence of a catalyst, at an initial temperature of 45°C. Equivalent TPU formulations with classical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…From the graph, the melting temperature, T m for PEPO was observed to be at 10 °C while HPEPO has higher in a range between 45 to 60 °C . As related to previous findings reported by Zhang et al [13] and Rashmi et al [14], bio-based polyols are typically have low melting temperature due the domain that consists of soft segments that crosslink to each other. According to Wang and Schuman [15], the composition of the polymer within the cross linked structure plays an important role in thermal behavior, with the inherently flexible structure of fatty acid chain in PEPO reducing the crosslink density to form a less compact crosslinked structure compared to HPEPO.…”
Section: Nmr Analysissupporting
confidence: 50%
“…From the graph, the melting temperature, T m for PEPO was observed to be at 10 °C while HPEPO has higher in a range between 45 to 60 °C . As related to previous findings reported by Zhang et al [13] and Rashmi et al [14], bio-based polyols are typically have low melting temperature due the domain that consists of soft segments that crosslink to each other. According to Wang and Schuman [15], the composition of the polymer within the cross linked structure plays an important role in thermal behavior, with the inherently flexible structure of fatty acid chain in PEPO reducing the crosslink density to form a less compact crosslinked structure compared to HPEPO.…”
Section: Nmr Analysissupporting
confidence: 50%
“…NAH and C@O hydrogen bonded and nonhydrogen bonded stretching vibrations observed at $3320, $1700, and $1725 cm 21 clearly indicate formation of the urethane group. The lack of an isocyanate peak at 2270 cm 21 and presence of the amine and carbonyl peaks indicate a complete conversion of monomers to urethane [19,42,43].…”
Section: Morphology and Thermal Conductivity Of Tpu/cnt Nanocompositesmentioning
confidence: 99%
“…The actual trends of green chemistry are connected with the replacing of petrochemical-based chemicals by bio-based and renewable feedstock. The increasing interest in the area of bio-based substances (e.g., polyols [1,2,15,16], chain extenders [17][18][19][20] and diisocyanates [21,22]) used as a components in the synthesis of polyurethanes is observed. According to the literature, the non-isocyanates polyurethanes synthesized using natural resources (e.g., vegetable oils, bio-based diamines, fatty acids and glycerol) are also known [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Susterra Ò is a completely bio-based diol obtained by biotechnological process from corn sugar. Rashmi et al [18] demonstrated that the replacement of petroleum-based chain extenders by biobased one like Susterra Ò was not reduced the properties of obtained materials, e.g., solubility, thermal and mechanical properties. Another bio-derived propanediol produced by DuPont Tate & Lyle BioProducts is Zemea Ò , which is also obtained in the fermentation process of the corn glucose.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation